Bollywood women and Indian society - Ambrish Saxena Ed (Kanishka pub, 2019)
Women have a distinguished place in Indian society and their status inside and outside home is always kept at a high pedestal. No doubt, we witness these days incidents of exploitation of women sexually and otherwise, but these could be aberrations. In India, family ties are strong and the focal point in these ties is women in different roles of mother, wife and sister.